2006
DOI: 10.2527/2006.842291x
|View full text |Cite
|
Sign up to set email alerts
|

Association of a single nucleotide polymorphism in the calpastatin gene with carcass and meat quality traits of beef cattle1

Abstract: Calpastatin (CAST) is a naturally occurring protein that inhibits the normal tenderization of meat as it ages postmortem. A SNP was identified in the CAST gene (a G to C substitution) and genotyped on crossbred commercially fed heifers (n = 163), steers (n = 226), and bulls (n = 61) from beef feedlots, and steers (n = 178) from a University of Guelph feeding trial. The association of the CAST SNP with carcass and meat quality traits was studied. Carcass traits included fat, lean, and bone yield; grade fat; LM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
139
2
26

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(175 citation statements)
references
References 13 publications
8
139
2
26
Order By: Relevance
“…However, it may be possible to fi nd linkage disequilibrium between this marker and functional polymorphisms in surrounding genes, as well as the possibility of pleiotropic effects. Chung et al (2001b) found signifi cant associations between CAST polymorphisms and percentage of kidney, pelvic and heart fat, and Schenkel et al (2006) associated the gene with carcass fat yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it may be possible to fi nd linkage disequilibrium between this marker and functional polymorphisms in surrounding genes, as well as the possibility of pleiotropic effects. Chung et al (2001b) found signifi cant associations between CAST polymorphisms and percentage of kidney, pelvic and heart fat, and Schenkel et al (2006) associated the gene with carcass fat yield.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the size of the effect, the association between CAST/XmnI and the evaluated traits may have been signifi cant with more animals in the sample. The weak linkage disequilibrium hypothesis showed that other polymorphisms described in the CAST gene were closely related to variation in meat tenderness, namely the SNP A2959G (access number AF159246), at region 3' UTR, and G/C (nucleotide 282 of access number AY008267), at intron 5, identifi ed by Barendse (2004) and Schenkel et al (2006) respectively. Curi et al (2008) reported the genotyping of A2959G (AF159246) SNP of bovine CAST gene by PCR-RFLP technique for the fi rst time.…”
Section: Resultsmentioning
confidence: 99%
“…Bunun yanı sıra koyunlarda da CAST geninde varyasyon olduğu bildirilmiştir (Palmer et al 1998;Sutikno et al 2011). PCR-RFLP metodu kullanılarak yapılan önceki çalışmalarda koyun CAST geninde 2 allel (M ve N) (Sutikno et al 2011;Palmer et al 1998), PCR-SSCP metodu kullanılarak yapılan çalışmalarda ise 3 allel (A, B, C) tanımlanmış ve C alleli ile et kalite özellikleri arasındaki ilişki olduğu bildirilmiştir (Schenkel et al 2006).…”
Section: Introductionunclassified
“…There are many factors that influence meat tenderness such as breeding, genetic, protein composition of muscle fibers, before and after slaughtering conditions (Dinh 2006). However, genetic studies on genetic factors affecting the degree of toughness of meat have indicated that Calpastatin (CAST) gene is an important DNA marker for meat quality traits (Schenkel et al 2006;Allais et al 2011). The calpaines play a key role in the process of meat tenderness with proteolytic activities in cold storage.…”
Section: Intrоduсtiоnmentioning
confidence: 99%